Analisis Aspek Usability dan User Experience Website dan Aplikasi Mobile Radio Streaming (Studi Pada Website dan Aplikasi Mobile Radio Prambors) - Muhammad Audi; Retno Indah Rokhmawati; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
This study aims to obtain the level of usability and user experience and the results of perceptions and interaction problems experienced by users using the Prambors Radio website and mobile applications . This research uses two analytical methods. First usability level analysis using scenario testing to eight respondents with age range 15-29 years in using Prambors Radio website and mobile application to measure usability aspect that aspect of effectiveness, efficiency, and user satisfaction. The second method is user experience level analysis using the UEQ (User Experience Questionnaire) questionnaire to thirty respondents to measure six scales: attractiveness, efficiency, perspicuity, dependability, stimulation and novelty and focus group discussion to gain perception, impression and interaction issues more detailed user. The results of the analysis show that in the usability level analysis, Prambors Radio websites and mobile application have a good level of effectiveness with a percentage of 100%, Prambors Radio website gets a better level of efficiency than Prambors Radio mobile application, and the level of user satisfaction with Prambors Radio mobile applications is bigger than Prambors Radio website. The result of user experience level analysis shows that the average value of each parameter of UEQ questionnaire on Prambors Radio website and Prambors Radio mobile application reaches â‰¥ 0.8. This indicates that respondents gave positive perceptions to Prambors Radio website and Prambors Radio mobile application.